Isomeric dithienophosphepines: the impact of ring fusion on electronic and structural properties - Padberg, Kevin; Ascherl, Johannes D. R.; Kivala, Milan (Chemistry - a European journal, 2020)
Abstract The synthesis and extensive experimental (X-ray crystallography, UV/Vis spectroscopy, cyclic voltammetry) and theoretical (DFT calculations) characterization of two isomeric dithieno[b,f]phosphepines (DTPs) are presented herein. The relative orientation of the phosphepine and the thiophene moieties has a decisive impact on the electronic and structural properties of these compounds. Moreover, the thiophene units allow for a facile subsequent functionalization through direct Pd-catalyzed C?H coupling, which renders DTPs highly promising building blocks for organophosphorus functional materials.
First published: 04 December 2019
Gesehen am 23.04.2020